Design, synthesis, and anti-cancer evaluation of new pyrido[2,3-d]pyrimidin-4(3H)-one derivatives as potential EGFRWT and EGFRT790M inhibitors and apoptosis inducers - Heba S. A. Elzahabi; Eman S. Nossier; Rania A. Alasfoury; May El-Manawaty; Sara M. Sayed; Eslam B. Elkaeed; Ahmed M. Metwaly; Mohamed Hagras; Ibrahim H. Eissa (Taylor & Francis Group, 2022)
A new series of pyrido[2,3-d]pyrimidin-4(3H)-one derivatives having the essential pharmacophoric features of EGFR inhibitors has been designed and synthesised. Cell viability screening was performed for these compounds against A-549, PC-3, HCT-116, and MCF-7 cell lines at a dose of 100 μM. The highest active derivatives (8a, 8 b, 8d, 9a, and 12b) were selected for IC50 screening. Compounds 8a, 8 b, and 9a showed the highest cytotoxic activities and were further investigated for wild EGFRWT and mutant EGFRT790M inhibitory activities. Compound 8a showed the highest inhibitory activities against EGFRWT and EGFRT790M with IC50 values of 0.099 and 0.123 µM, respectively. In addition, it arrested the cell cycle at pre-G1 phase and induced a significant apoptotic effect in PC-3 cells. Furthermore, compound 8a induced a 5.3-fold increase in the level of caspase-3 in PC-3 cells. Finally, docking studies were carried out to examine the binding mode of the synthesised compounds against both EGFRWT and EGFRT790M.